PENGEMBANGAN BAHAN AJAR MATERI PEMBELAJARAN MATEMATIKA SD DENGAN PENDEKATAN REALISTIK BERNUANSA ISLAMI UNTUK MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Ida Nurmila Isandespha (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This research is a development research, which was developed by Borg & Gall, that aims ofthis study are to determine the measures and feasibility of teaching material’s development ofelementary mathematics learning with Islamic nuance realistic approach for PGSD students. Thisresearch has only reached the first stage of development, i.e. validation expert. The research draftof this development consists of three stages: 1) a preliminary study, 2) planning, and 3) the initialproduct development and validation experts. The research instrument used validation sheet ofmaterial expert and validation sheet of media experts. Descriptive statistics technique was used toanalyze the data. Based on the results of the feasibility study by the experts concluded that theteaching materials developed has eligibility as follows: (1) feasibility of the contents in accordancewith the material scope and the competence level of elementary mathematics learning materials,(2) the feasibility of presentation, (3) the feasibility of the language, (4) implementate amathematical realistic approach with Islamic nuance, and (5) the feasibility of teaching material.